The pharmacists' awareness, knowledge and attitude about childhood autism in Istanbul - ÜNAL, ÇAĞRI; KARAVUŞ, MELDA; ÇELİK, MEHMETHAN; LÜLECİ, NİMET EMEL; HIDIROĞLU, SEYHAN (SPRINGER, 2016)
Background Being one of the key players in healthcare, pharmacists could have an important role in the early detection and care of children with autism, by familiarizing themselves with autism-related resources and helping families to find relevant professional resources. Objective The purpose of this study was to determine the awareness of pharmacists about autism, and their knowledge and attitude towards autism. Setting A degrees stanbul Province of Turkey. Method This descriptive study was carried out in pharmacists working in Istanbul Province of Turkey in 7 municipalities out of 39. One hundred forty-one out of 150 pharmacists who agreed to participate in our study were interviewed with the help of questionnaires. Main outcome measure Knowledge about childhood ASD and the social characteristics thereoff amongst pharmacists. Results Minimum 33.4 and maximum 73.1 % of the pharmacists gave correct answers to each question. Furthermore pharmacists' knowledge about causative factors of childhood ASD proved to be lacking and they tend to believe in outdated theories. The percentage of pharmacists believing that autism holds social stigma in this community was 66.0 %. Conclusion Pharmacists' knowledge regarding ASD needs to be improved. Enhancing their awareness, especially about basic social characteristics of childhood ASD will help pharmacists direct families of children with ASD to responsible health authorities.
Keywords: Attitude; Autism; Awareness; Childhood; Knowledge; Pharmacists; Turkey; CHILDREN